The rough sheath2 gene negatively regulates homeobox gene expression during maize leaf development. - Schneeberger, R; Tsiantis, M; Freeling, M; Langdale, J (1998)
Leaves of higher plants are produced in a sequential manner through the differentiation of cells that are derived from the shoot apical meristem. Current evidence suggests that this transition from meristematic to leaf cell fate requires the down-regulation of knotted1-like homeobox (knox) gene expression. If knox gene expression is not repressed, overall leaf shape and cellular differentiation within the leaf are perturbed. In order to identify genes that are required for the aquisition of leaf cell fates, we have genetically screened for recessive mutations that confer phenotypes similar to dominant mutations (e.g. Knotted1 and Rough sheath1) that result in the ectopic expression of class I knox genes. Independently derived mutations at the rough sheath2 (rs2) locus condition a range of pleiotropic leaf, node and internode phenotypes that are sensitive to genetic background and environment. Phenotypes include dwarfism, leaf twisting, disorganized differentiation of the blade-sheath boundary, aberrant vascular patterning and the generation of semi-bladeless leaves. knox genes are initially repressed in rs2 mutants as leaf founder cells are recruited in the meristem. However, this repression is often incomplete and is not maintained as the leaf progresses through developement. Expression studies indicate that three knox genes are ectopically or over-expressed in developing primordia and in mature leaves. We therefore propose that the rs2 gene product acts to repress knox gene expression (either directly or indirectly) and that rs2 gene action is essential for the elaboration of normal leaf morphology.